Social and Individual Subjective Wellbeing and Capabilities in Chile - González, Pablo A.; Dussaillant, Francisca; Calvo, Esteban (Frontiers in Psychology, 2021)
The notion of social belongingness has been applied to different scales, from individual to social processes, and from subjective to objective dimensions. This article seeks to contribute to this multidimensional perspective on belongingness by drawing from the capabilities and subjective wellbeing perspectives. The specific aim is to analyze the relationships between capabilities – including those related to social belongingness - and individual and social subjective wellbeing. The hypotheses are: (H1-H2) There is a relationship between capabilities (measured as evaluation and functioning) and (H1) individual and (H2) social subjective wellbeing; (H3) The set of capabilities associated to individual subjective well being differs from the set correlated to social subjective wellbeing; (H4) The intensity and significance of the correlation between subjective wellbeing and capabilities depends on whether the later is measured as evaluation or functioning; and (H5) The relationships between capabilities and subjective wellbeing are complex and nonlinear. Using a nationally representative survey in Chile, multiple linear (H1-H5) and dose response matching (H1-H5) regressions between capabilities and subjective wellbeing outcomes are estimated confirming all hypotheses. Subjective evaluations and effective functionings of some capabilities (‘basic needs’, ‘social ties’, ‘feeling recognized and respected’; ‘having and deploying a life project’) are consistently correlated with both subjective wellbeing outcomes. Others capabilities are correlated with both subjective wellbeing outcomes only when measured as functionings (contact with nature), do not display a systematic pattern of correlation (‘health’, ‘pleasure’, ‘participation’, and ‘human security’) or are not associated with subjective wellbeing (‘self-knowledge’ and ‘understanding the world’). When observed, correlations are sizable, nonlinear, and consistent across estimation methods. Moreover, capabilities related to social belongingness such as ‘social ties’ and ‘feeling recognized and respected’ are important by themselves but also are positively correlated to both social and individual subjective wellbeing. These findings underscore the need of a multidimensional perspective on the relationships between capabilities and subjective wellbeing, considering both subjective and objective, as well as individual and social aspects that are relevant to belongingness. These findings also have practical and policy implications, and may inform public deliberation processes and policy decisions to develop capabilities, promote subjective wellbeing, and ultimately promote positive belongingness.